SELECTION OF A1 AND A2 LEVEL VOCABULARY FOR LEARNERS OF UZBEK AS A FOREIGN LANGUAGE - Malika Axmadjanova Maxmudjon qizi (Western European Studies, 2025)
In recent years, interest in learning Uzbek as a foreign language has increased, particularly among students, researchers, and diplomats focused on Central Asia. However, teaching resources remain limited, especially regarding level-appropriate vocabulary. This study aims to develop a vocabulary list tailored for A1 and A2 learners of Uzbek based on the Common European Framework of Reference for Languages (CEFR). Using a mixed-methods approach, including corpus analysis, curriculum review, thematic categorization, and CEFR alignment, we identified high-frequency and communicatively essential lexical items suitable for beginner learners. The study highlights the absence of an official Uzbek lexical minimum, underscoring the need for standardized vocabulary guidelines to enhance curriculum design, teaching consistency, and learner outcomes. Establishing a scientifically grounded lexical minimum aligned with CEFR standards will support the gradual development of language competence and facilitate the integration of Uzbek language instruction into international frameworks. The findings provide a foundational resource for educators, curriculum developers, and digital language learning tools aimed at beginner Uzbek learners
Keywords: Uzbek language; foreign language learning; vocabulary list